2022
DOI: 10.3390/nu14102067
|View full text |Cite
|
Sign up to set email alerts
|

Inner Shell of the Chestnut (Castanea crenatta) Suppresses Inflammatory Responses in Ovalbumin-Induced Allergic Asthma Mouse Model

Abstract: The inner shell of the chestnut (Castanea crenata) contains various polyphenols, which exert beneficial biological effects. Hence, we assessed the anti-inflammatory efficacy of a chestnut inner shell extract (CIE) in ovalbumin (OVA)-induced allergic asthma. We intraperitoneally injected 20 ug of OVA with 2 mg of aluminum hydroxide on days 0 and 14. On test days 21, 22, and 23, the mice were treated with aerosolized 1% (w/v) OVA in saline. CIE was administered orally at 100 and 300 mg/kg on days 18–23. CIE sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…To obtain BALF from mice, the mice were sacrificed by carbon dioxide inhalation 24 h after the last CSC exposure. Tracheostomy and BALF sampling were performed according to previously published methods [ 19 ]. Macrophage counts in BALF were determined using Diff-Quik® staining reagent (Sysmex Corporation, Kobe, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…To obtain BALF from mice, the mice were sacrificed by carbon dioxide inhalation 24 h after the last CSC exposure. Tracheostomy and BALF sampling were performed according to previously published methods [ 19 ]. Macrophage counts in BALF were determined using Diff-Quik® staining reagent (Sysmex Corporation, Kobe, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…The mice were randomly divided into six groups ( n = 8 per group): group A, control (normal diet + 0.9% saline daily via oral gavage); group B, high-fat diet (HFD; HFD + 0.9% saline daily via oral gavage) (Jiangsu Synergetic Pharmaceutical Biological Engineering Co., Ltd, Nanjing, China); group C, HFD + orlistat (HFD + 15.6 mg orlistat per kg body weight (O159936, Aladdin, Shanghai, China)) daily via oral gavage; group D, HFD + CSP (HFD + 300 mg CSP per kg body weight daily via oral gavage); group E, HFD + AG490 (HFD + 1 mg (dissolving with 10% DMSO) AG490 per kg body weight [A126525, Aladdin] intraperitoneally every three days); and group F, HFD + AG490 + CSP (HFD + 1 mg AG490 per kg body weight intraperitoneally every three days + 300 mg CSP per kg body weight daily via oral gavage). 26 AG490 is a JAK2 protein tyrosine kinase inhibitor. The HFD comprised 20% proteins, 35% carbohydrates, and 45% fat.…”
Section: Methodsmentioning
confidence: 99%
“…For example, dietary supplementation of BerriQi ® Boysenberry and apple juice concentrate, containing high amounts of anthocyanins, ellagitannins, and chlorogenic acids, in OVA-challenged asthmatic mice can suppress immune cell infiltration in the lung, tissue damage, and mucus production as a result of regulation of innate immune pathways [295]. Similarly, the chestnut inner shell extract, as a rich source of gallic acid (a phenolic acid) and ellagic acid (a tannin), was found to present the anti-asthmatic efficacy inhibiting the inflammatory response induced by OVA challenge and relieving asthma symptoms, such as airway hyperresponsiveness and mucus overproduction in the asthma mice model [296]. Therapeutic properties of magnolol, an active polyphenol extracted from Magnolia officinalis, which is traditionally used in Chinese medicine for the treatment of asthma and cough, were also confirmed in studies on OVA-induced asthmatic mice models that showed significant suppression of allergen-induced airway hyperactivity and inflammation along with reduction in lung tissue eosinophil infiltration, mucus overproduction, and collagen deposition [297,298].…”
Section: Asthmamentioning
confidence: 99%